2016
DOI: 10.1371/journal.pone.0148656
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of Proliferation and Apoptotic Markers in Papillary Thyroid Carcinoma: An Automated Analysis

Abstract: IntroductionProliferation and apoptosis are opposing processes by which the cell numbers are kept in a delicate balance, essential for tissue homeostasis, whereas uncontrolled growth of cells is a hallmark of cancer. Papillary thyroid cancer (PTC) is the commonest type of thyroid cancer, with some PTC following an indolent course, whereas the other ones are more aggressive.AimTo evaluate respective contribution of proliferation and apoptosis in the tumorigenesis of PTC by automated analysis.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A subset of studies compared the automated assessment of cytological and histological slides to manual assessment by a pathologist, reporting high correlation values between these two modalities with polyserial correlation coefficient, linear correlation coefficient, and area under the curve . In some studies, there was only a descriptive report of high correlation without measures .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of studies compared the automated assessment of cytological and histological slides to manual assessment by a pathologist, reporting high correlation values between these two modalities with polyserial correlation coefficient, linear correlation coefficient, and area under the curve . In some studies, there was only a descriptive report of high correlation without measures .…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies, automated algorithms were applied to quantify cellular parameters such as percentage of stained area, number of stained cells, intensity of staining for immunohistochemistry, and nuclear features in cytology studies . Three studies from a Belgian group explored the expression of various immunohistochemical markers in partially overlapping cohorts of cases with PTC, follicular variant of PTC (FVPTC), thyroid neoplasm with uncertain malignant potential, normal tissue and adenomatous lesions, both with or without semi‐quantitative assessment by the pathologist. In one study by this group, there was also a comparison between two AI models for immunohistochemistry assessment, in which the authors stressed that their algorithms provide results in the form of continuous data, that are easier to manipulate with statistics and to compare with results from other studies .…”
Section: Resultsmentioning
confidence: 99%
“…Deregulated cell cycle is one of the most consistently observed events in human cancers, including PTC [14][15][16] . A previous study from Kuo et al showed that exogenous CXCL5 induced a decrease in CDKN1B and an increase in CDK4 in prostate cancer cells 17 , promoting us to decipher the role of CXCL5-CXCR2 in the cell cycle progress of PTC cells.…”
Section: Discussionmentioning
confidence: 99%
“…9). However, increased cleaved capsase-3 activity has been shown to be elevated in metastatic thyroid carcinomas compared to normal thyroid tissue [55]. Tumors treatment with the drug-loaded MSN showed lower expression of the epithelialmesenchymal transition (EMT) marker vimentin (VIM), indicating lower invasiveness and metastatic potential of these ML-1 xenografts [56].…”
Section: In Vivo Drug Efficacy Studies Utilizing Chick Chorioallantoi...mentioning
confidence: 99%